The Mediating role of attitudes towards performing well between ethical leadership, technological innovation, and innovative performance - Hassan Danial Aslam; Sorinel Căapuşneanu; Tasawar Javed; Ileana-Sorina Rakos; Cristian-Marian Barbu (Administrative Sciences, 2024)
The business sector is rife with unethical managerial practices, such as blaming subordinates for organizational failings, along with the exploitation of colleagues, favoritism, and conflicts of leadership. In light of this, numerous researchers have endeavored to explain the phenomenon of ethical perspectives and concerns. It is recommended that organizations in the SME sector adopt ethical practices in order to achieve their long-term objectives. This study stresses the influence of ethical leadership and technological innovation, particularly the mediating role of a positive attitude in encouraging good performance. This study, which was conducted in the SME sector of Malaysia in the state of Selangor, employed a convenience sampling technique for data collection and reports that ethical leadership, technological innovation, and attitude significantly influence performance. A mediating role of attitude in relation to technological innovation and innovative performance is hereby reported, and attitude towards performance was found to have an insignificant effect on ethical leadership and innovative performance. This study contributes to the existing body of knowledge by explaining the role of ethical leadership and technological innovation in expressing and assessing the revolutionary business practices required to ensure organizational success.
Keywords: 350; innovative performance; ethical leadership; technological innovation; attitudes towardsperforming well; SME